Pengaruh Manajemen Risiko Dengan Good Corporate Governance Sebagai Variabel Moderating Terhadap Kinerja Keuangan BRI Syariah Periode 2015-2019 - Syafi Nazariyah; Mukhamad Roni; Nurul Azizah Ria Kusrini (Journal of Islamic Banking, 2021)
Good and bad pictures of a company regarding the level of success achieved can be seen from the financial performance of a company. Banking institutions have a high level of complexity and risk, so applying a good risk management system can improve bank financial performance with through Good Corporate Governance. This study aims to determine the effect of risk management as measured by the NPF ratio to measure financing risk, BOPO to measure operational risk and CAR to measure capital adequacy on financial performance as measured by ROA, ROE and NPM ratios and to determine the effect of GCG as measured by the size of the board of commissioners, the size of the board of directors, the size of the audit committee and the size of the sharia supervisory board as a moderating variable for risk management on the financial performance of BRI Syariah banks for the period 2015-2019. This study used quantitative research methods. and analysed data using Partial Least Square Software, namely the SmartPLS version 2 program. The results of this study indicate that risk management as measured by the NPF, BOPO and CAR ratios has a significant negative effect on financial performance at BRI Sharia Banks and GCG has not been able to moderate risk management on financial performance.